1979
DOI: 10.1007/bf02671759
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetallic palladium‐on‐resin: A very active and selective catalyst for the hydrogenation of diunsaturated fatty acid esters I

Abstract: Me t by1 cis-9,cis-I 2-octadecadienoate (methyl linoleate; e9,c12) and the corresponding eis, trans and trans, trans geometric isomers (c9,t12 and t9,t12) were hydrogenated at 40 C and atmospheric hydrogen pressure in acetone as solvent, with nonmetallic palladium-on-resin catalyst. These catalysts were prepared by impregnation of cationic exchange resins with an aqueous solution of palladium dichloride. The methyleneinterrupted dienes were hydrogenated to the monoene stage with almost infinite selectivity, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Isomerization of vegetable oil, whose primary constituent is linoleic acid, is an important reaction which finds applications mainly in the coating industries. A number of papers describe the isomerization process using homogeneous and heterogeneous catalysts (de Jarlis and Cast, 1971); Vanderplank et al, 1979). Rhodiumand ruthenium-supported catalysts have been used for the isomerization of sunflower oil and methyl linoleate (Cecchi ; Ucciani and Cecchi, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Isomerization of vegetable oil, whose primary constituent is linoleic acid, is an important reaction which finds applications mainly in the coating industries. A number of papers describe the isomerization process using homogeneous and heterogeneous catalysts (de Jarlis and Cast, 1971); Vanderplank et al, 1979). Rhodiumand ruthenium-supported catalysts have been used for the isomerization of sunflower oil and methyl linoleate (Cecchi ; Ucciani and Cecchi, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A number of heterogeneous and homogeneous catalyst systems have been reported for the isomerization of methyl linoleate (Cecchi and Ucciani, 1981; Dejaríais and Cast, 1971a,b;Deshpande et al, 1985;Koritala et al, 1970a,b; Ucciani and Cecchi, 1981;Vanderplank et al, 1979). It is found that, among the ruthenium-based catalysts, ruthenium chloride anchored on supports like alumina, silica-alumina, etc., is very active for the isomerization reaction (Narasimhan et al, 1985a).…”
mentioning
confidence: 99%
“…Methyl linoleate, the chief constituent of safflower oil, can be isomerized with a variety of homogeneous or heterogeneous catalysts (Cechi and Ucciani, 1981; Ucciani and Cechi, 1981). The isomerization of methyl linoleate on several homogenous and metal oxide catalysts (Dejaríais and Cast, 1971a,b; Dolev et al, 1972) and the double bond migration and hydrogenation of methyl oleate, the ester of the monoenic acid, have been well studied (Vender Plank et al, 1979; Gut et al, 1979;Dutton et al, 1968; Zwicky and Gut, 1978; Grau et al, 1986). We had reported earlier (Deshpande et al, 1985; Mukesh et al, 1985) on the kinetics and mathematical modeling of isomerization of methyl linoleate with ruthenium on carbon catalyst in the presence of a hydrogen donor solvent in an autoclave.…”
mentioning
confidence: 99%